Prevalence of Cardiac Arrhythmias During and After Pregnancy in Women with Chagas' Disease without Apparent Heart Disease - Achá Renato Enrique Sologuren; Rezende Marco Túlio Oliveira; Guzmán Heredia Rimmel Amador; Silva Aguinaldo Coelho da; Rezende Elmiro Santos; Souza Cleber Augusto Oliveira (Arquivos Brasileiros de Cardiologia, 2002)
OBJECTIVE: To evaluate cardiac arrhythmias during and after pregnancy in women with Chagas' disease without apparent heart disease using dynamic electrocardiography. METHODS: Twenty pregnant women with Chagas' disease without apparent heart disease aged 19 to 42 years (26.96 ± 3.6) and a control group of 20 non-chagasic pregnant patients aged 16 to 34 years (22.5 ± 4.8). The patients were submitted to passive hemagglutination and indirect immunofluorescence for the detection of Trypanosoma cruzi evaluation, and electrocardiography, echocardiography and 24-h dynamic electrocardiography. RESULTS: Supraventricular premature depolarizations were observed in 18 (90%) patients and ventricular premature depolarization in 11 (55%) patients of both groups during pregnancy. After delivery, supraventricular premature depolarizations were present in 13 (60%) chagasic patients and in 16 (89.4%) control patients (P<=0.05). Ventricular premature depolarization were observed in 9 (45%) chagasic patients and 11 (57.8%) control patients. CONCLUSION: The prevalence of ventricular premature depolarization was similar for the chagasic and control groups during and after pregnancy. The incidence of supraventricular premature depolarizations was similar in the two groups during pregnancy, while after delivery a predominance was observed in the control group compared to the chagasic group.